2011
DOI: 10.1002/dvdy.22671
|View full text |Cite
|
Sign up to set email alerts
|

The functions of maternal Dishevelled 2 and 3 in the Early Xenopus embryo

Abstract: Of the three Dishevelled (Dvl) genes, only Dvl2 and Dvl3 are maternally encoded in the frog, Xenopus laevis. We show here by loss of function analysis that single depletion of either Dvl2 or Dvl3 from the oocyte causes the same embryonic phenotype. We find that the effects of loss of function of Dvl2 and 3 together are additive, and that the proteins physically interact, suggesting that both are required in the same complex. We show that maternal Dvl2 and 3 are required for convergence extension movements down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…All RT-PCR results are presented as percentages compared with the levels in uninjected embryos after normalization to the expression of ornithine decarboxylase ( odc ). Embryos were cultured and processed for whole-mount ISH using a protocol described previously [51]. Sense and antisense par6b Dig-labeled RNA probes were synthesized using Ambion MEGA script kits and digoxygenin-11-UTP.…”
Section: Methodsmentioning
confidence: 99%
“…All RT-PCR results are presented as percentages compared with the levels in uninjected embryos after normalization to the expression of ornithine decarboxylase ( odc ). Embryos were cultured and processed for whole-mount ISH using a protocol described previously [51]. Sense and antisense par6b Dig-labeled RNA probes were synthesized using Ambion MEGA script kits and digoxygenin-11-UTP.…”
Section: Methodsmentioning
confidence: 99%
“…Ad hoc T-test (pval<0.05) demonstrated that a putative DVL3 transcript was higher in released oocytes, suggesting the importance of this molecule in bivalve oocyte maturation. The protein encoded by DVL3 gene is implicated in transduction signal ( Figure 3 ) conveyed by various WNT genes and, in Xenopus oocytes, its expression has been reported to be extremely important for transduction of canonical WNT signals after fertilization [62] . To conclude, the hypothesis that in V. decussata oocytes the amount of mRNAs encoding proteins involved in WNT signalling could be extremely important to complete oocyte maturation and fertilization is a matter of concern for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, DVL2 −/− DVL3 +/− and DVL1 −/− DVL2 −/− mice display much more severe NTD than DVL2 −/− mice (Hamblet et al, 2002; Wang et al, 2006; Etheridge et al, 2008), which strongly suggests that DVL1 and DVL3 contribute directly or indirectly to neural tube closure. Along this line, maternal single knock-down of either DVL2 or DVL3 in Xenopus caused NTD (Tadjuidje et al, 2011), supporting a contribution of DVL2 and DVL3.…”
Section: Dvl Paralogs In Vertebrate Embryonic Developmentmentioning
confidence: 94%
“…In early Xenopus embryos, DVL2 and DVL3 are present maternally, whereas DVL1 expression is upregulated after the mid-blastula transition (Tadjuidje et al, 2011). At early gastrula stages, all three DVL paralogs are expressed in the prospective mesoderm including Spemann's organizer and, although weaker, in the ectoderm.…”
Section: Dvl Paralogs In Vertebrate Embryonic Developmentmentioning
confidence: 99%